STRATEGI MENINGKATKAN KEMAMPUAN PSIKOMOTORIK SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Megawati Megawati; Chaerul Rochman (PEDAGOGIK : JURNAL PENDIDIKAN, 2019)
This study aims to study the ability of students strategies subjects PAI of the SMP Al-Ishlah Bekasi in the psychomotor. The results of this study indicate that the psychomotor abilities of students in PAI subjects at the SMP Al-Ishlah Bekasi are not optimal. The strategies to improve students' psychomotor abilities include: the need for routine/extracurricular activities in the Quran reading and writing in schools, the need for the habit of reading the Quran during PAI lessons, the application of Quran-based education.